A near-infrared fluorescent probe based on corrole derivative with large Stokes shift for detection of hydrogen sulfide in water and living cells. (August 2022) - Lu, Guifen; Gao, Yongjie; Wang, Xiaochun; Zhang, Dianqi; Meng, Suci; Yu, Siyuan; Zhuang, Yanfang; Duan, Luyao
Abstract: A distinct near-infrared (NIR) fluorescent probe (COR-DNBS ), based on corrole derivative, was designed and synthesized for detection of hydrogen sulfide (H2 S) by the photoinduced electron transfer (PET) mechanism. Probe COR-DNBS was constructed by 5, 15-di(4-chlorophenyl)-10-(4-hydroxylphenyl)-corrole (COR-OH ) as fluorophore and 2, 4-dinitrobenzenesulfonyl ether (DNBS) as recognition site. The chemical structure of COR-DNBS was fully characterized by 1 H NMR, 13 C NMR, EA, IR and mass spectrometry. COR-DNBS showed a high selectivity and an excellent sensitivity to H2 S with a detection limit of 28 nM together with a fast response (46 s). Importantly, it also exhibited a large Stokes shift (231 nm) and red emission (656 nm), which is highly desirable for bioimaging applications. The sensing mechanism was proved to be H2 S triggered thiolysis reaction by 1 H NMR, HRMS and the DFT calculations. In the present work, successful detection and bioimaging of H2 S in water and living cells was achieved. Moreover, COR-DNBS could be used as a paper test strip for monitoring and screening of H2 S in environment. Graphical abstract: Image 1 Highlights: A new corrole-based NIR fluorescent probe COR-DNBS was developed for the detection of H2 S. COR-DNBS emitted in the red region with an ultra-large Stokes shift (231 nm). COR-DNBS exhibited high selectivity and sensitivity towards H2 S (LOD: 28 nm). COR-DNBS was exploited for the visualization of H2 S in solution and living cells.